2020
DOI: 10.1182/blood-2020-137800
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Incidence and Risk Factors Associated with Major Cardiovascular Events in Patients Receiving Acalabrutinib Therapy

Abstract: Background Acalabrutinib is a highly selective second-generation Bruton's tyrosine kinase (BTK) inhibitor approved for the treatment of chronic lymphocytic leukemia (CLL) and mantle cell lymphoma. Ibrutinib, the first-generation nonselective BTK inhibitor, has been associated with cardiovascular (CV) complications including atrial fibrillation and ventricular arrhythmias, potentially related to off-target effects. In prior studies, the incidence of major adverse cardiovascular effects (MACE) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… 15 Similar observations were noted in a preliminary acalabrutinib report. 16 In cardiac-focused studies, the presence of left atrial remodeling, marked by atrial dilation, significantly increased the risk for ibrutinib-associated AF events. 11 , 17 The presence of pre-existing cardiovascular disease (CVD) also appears to confer an increased risk of AF events.…”
Section: Btk Inhibitor-associated Afmentioning
confidence: 99%
See 3 more Smart Citations
“… 15 Similar observations were noted in a preliminary acalabrutinib report. 16 In cardiac-focused studies, the presence of left atrial remodeling, marked by atrial dilation, significantly increased the risk for ibrutinib-associated AF events. 11 , 17 The presence of pre-existing cardiovascular disease (CVD) also appears to confer an increased risk of AF events.…”
Section: Btk Inhibitor-associated Afmentioning
confidence: 99%
“…25 Notably, in an evaluation of acalabrutinib-treated hematologic malignancy patients, the development of incident AF and other cardiac events is associated with worse long-term survival. 16 …”
Section: Btk Inhibitor-associated Afmentioning
confidence: 99%
See 2 more Smart Citations
“…In one meta-analysis of 1,505 ibrutinib-treated patients, age (older than 65) and history of atrial fibrillation were associated with the risk of developing ibrutinib-related atrial fibrillation [ 9 ]. Another study found that history of atrial fibrillation and Framingham Heart Study AF risk score were significantly associated with the development of atrial fibrillation [ 10 ], whereas a similar study found that heart failure and left atrial abnormality on electrocardiogram were independent predictors of atrial fibrillation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%